Fundamental principles in bacterial physiology—history, recent progress, and the future with focus on cell size control: a review. (28th February 2018) - Jun, Suckjoon; Si, Fangwei; Pugatch, Rami; Scott, Matthew
Abstract: Bacterial physiology is a branch of biology that aims to understand overarching principles of cellular reproduction. Many important issues in bacterial physiology are inherently quantitative, and major contributors to the field have often brought together tools and ways of thinking from multiple disciplines. This article presents a comprehensive overview of major ideas and approaches developed since the early 20th century for anyone who is interested in the fundamental problems in bacterial physiology. This article is divided into two parts. In the first part (sections1 –3 ), we review the first 'golden era' of bacterial physiology from the 1940s to early 1970s and provide a complete list of major references from that period. In the second part (sections4 –7 ), we explain how the pioneering work from the first golden era has influenced various rediscoveries of general quantitative principles and significant further development in modern bacterial physiology. Specifically, section4 presents the history and current progress of the 'adder' principle of cell size homeostasis. Section5 discusses the implications of coarse-graining the cellular protein composition, and how the coarse-grained proteome 'sectors' re-balance under different growth conditions. Section6 focuses on physiological invariants, and explains how they are the key to understanding the coordination between growth and the cell cycle underlying cell size control in steady-state growth. Section7 overviews how the temporal organization of all the internal processes enables balanced growth. In the final section8, we conclude by discussing the remaining challenges for the future in the field.